2005
DOI: 10.1080/13651500510029020
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of attempted suicide in the elderly: The role of cognitive impairment

Abstract: The authors' aim was to assess the prevalence and importance of dementia and cognitive impairment in relation to suicidal behaviour in elderly psychiatric inpatients. The level of cognitive functioning (according to the Mini Mental State Examination - MMSE) of the elderly suicidal inpatients (N=62) were compared to the general elderly inpatients (N=152). There were significant differences in cognitive functioning between the two groups, in the non-suicidal group the level of cognitive function was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…In patients older than 65 years of age hospitalized in a psychiatric unit following SA, SA was positively associated with comorbid psychiatric disorders and history of SA. Moreover, the risk for suicidal behaviors decreases when cognitive impairment increases, based on to the Mini Mental State Examination (MMSE) score (Osvath et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…In patients older than 65 years of age hospitalized in a psychiatric unit following SA, SA was positively associated with comorbid psychiatric disorders and history of SA. Moreover, the risk for suicidal behaviors decreases when cognitive impairment increases, based on to the Mini Mental State Examination (MMSE) score (Osvath et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, dementia has been found to be associated with an elevated risk of attempted suicide compared with that of the general population of the same age (Lawrence et al ., 2000). Mild cognitive impairment and mild dementia were found to be common in older suicide attempters (Osvath et al ., 2005). Higher daily functioning and previous suicide attempts have been found to be associated with self-harm in AD.…”
Section: Resultsmentioning
confidence: 99%
“…In most studies suicide, self-harm and suicidal ideation are more frequent in mild dementia (Forsell et al ., 1997; Barak and Aizenberg, 2002; Osvath et al ., 2005). Among nursing home suicides, none occurred in those with severe cognitive impairment (Menghini and Evans, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Two systematic reviews that covered the published studies of attempted suicide and DSH in older people from 1985 to 2004 found that most studies reported less than 10% of patients had a primary diagnosis of dementia (Draper, 1996;Chan et al, 2007). Higher rates of dementia appear in studies that report psychiatric comorbidity (Sendbuehler and Goldstein, 1977;Draper, 1994;Schmid et al, 1994;Osvath et al, 2005). Where clinical details are provided, the majority of suicide attempts by people with dementia have psychiatric comorbidity, which mainly involves depression and/or psychosis (Batchelor and Napier, 1953;O'Neal et al, 1956;Sendbuehler and Goldstein, 1977;Draper, 1994;Schmid et al, 1994;Osvath et al, 2005;Tsai et al, 2007).…”
Section: Deliberate Self-harm (Dsh) and Attempted Suicidementioning
confidence: 99%